Weak ferromagnetism and magnetoelectric coupling through the spin–lattice coupling in (1−x)Pb(Fe2/3W1/3)O3–(x)BiFeO3 (x = 0.1 and 0.4) solid solution. (27th July 2020) - I, Shivaraja; Matteppanavar, Shidaling; Krishna, P S R; Rayaprol, Sudhindra; Babu, P D; Angadi V, Jagadeesha; Kubrin, S P; Angadi, Basavaraj
Abstract: We report on the structure, spin–lattice and magneto-electric coupling in (1− x )Pb(Fe2/3 W1/3 )O3 –( x )BiFeO3 (where x = 0.1 and 0.4) (PBFW) solid solution synthesized through two-step solid-state reaction method. The room temperature (RT) crystallographic studies were carried out using x-ray diffraction and neutron diffraction measurements which show a single-phase Pseudocubic crystal system with Pm -3 m space group. Rietveld refinement was carried out to obtain the structural parameters using Fullprof software and the observed structural parameters are in good agreement with the previous reports. Temperature-dependent neutron diffraction measurements reveal the presence of commensurate G-type antiferromagnetic structure. The magnetic structure was analyzed using the propagation wave vector k ∼ (½ ½ ½) for both the solid solutions. The obtained lattice constants increase linearly and the magnetic moment decrease with temperature, which shows a remarkable anomaly around the magnetic ( T N ∼ 405 K for x = 0.1 and 531 K for x = 0.4) transition temperatures. This anomaly clearly indicates the existence of spin–lattice and magnetoelectric coupling. The magnetic susceptibility (ZFC and FC at 500 Oe) and M – H hysteresis loop measurements show spontaneous magnetic moment due to the Fe 3+ –O 2− –Fe 3+ superexchange interaction coexisting with the weak ferromagnetism. Bifurcation of ZFC and FC curve reveals the strong anisotropic nature. Astonishingly, magnetic measurements show the non-zero magnetic moment above T N and broadening of the magnetic transition indicates the presence of short-range uncompensated sublattice weak ferromagnetic clusters in the paramagnetic region. The Mossbauer spectroscopy and electron paramagnetic resonance studies exhibit the RT magnetically ordered system and confirm the +3 state of Fe along with the fraction of Fe 2+ ions.